Інноваційні освітні технології у вищих навчальних закладах - Гуревич, Роман Семенович; Кадемія, Майя Юхимівна (НТУ "ХПІ", 2016)
У статті розглянуті підходи до здійснення інноваційного процесу навчання у ВНЗ – дистанційного навчання, його складових та різних моделей організації навчального процесу. Особливе місце відводиться використанню інформаційно-комунікаційних технологій. Розроблення та впровадження інтелектуальних навчальних систем на основі ІКТ сприятиме підвищенню якості професійної освіти у ВНЗ. Особлива увага приділена використанню інтерактивного навчального середовища.

The article deals with the implementation of innovative approaches to the learning process at the university – distance learning, its components, as well as different models of school organization. Special attention is paid to information and communication technologies, social networking Web 2.0. Development and implementation of intelligent tutoring systems based on ICT will improve the quality of vocational education at the university. Particular attention is paid to the use of interactive learning environment. Thus, the use of innovation in the training of future specialists will contribute to their adaptation to the rapid changes in society, science, business and education.
Innovative educational technologies in higher educational institutions
Keywords: дистанційне навчання; модульна технологія навчання; ВНЗ; інновація освіти; distance learning